Study on the Loading and Deformation of Tunnel Segments in Soft Clay with Consideration for the Soil Mass Rheological Characteristics - Li, Chunlin (Geotechnical and geological engineering, 2019)
A nonlinear visco-elastic–plastic creep constitutive model is established combined with a Bingham creep model and a Kelvin creep model. Additionally, the soil creep parameters of an undisturbed soil specimen from the Wuxi subway engineering investigation site are determined according to triaxial creep testing using the ordinary least square algorithm. The ground characteristic curves considering the time effect are proposed by combing the creep equation and cavity expansion theory. Finally, the change laws of segment support force and segment deformation as a function of time were investigated through a case study of a section of the Wuxi Subway Line No. 1, and the proposed analytical solution and numerical modeling provide consistent results for tunnel lining pressure.